Integration of Islamic Values in Early Childhood Education: A Comprehensive Framework - Vika Fransisca (Al-Banat: Journal of Early Childhood Islamic Education, 2024)
This research aims to develop a comprehensive framework in the integration of Islamic values in early childhood education (PAUD), in order to support the formation of Islamic character, morals, and ethics from an early age. A qualitative approach with a case study method is applied to five early childhood education institutions in Indonesia that have implemented Islamic values in their curriculum. Data was collected through in-depth interviews, observations, and documentation analysis of school principals, teachers, and parents. The results of the study show that these early childhood education institutions use exemplary methods, Islamic storytelling, and play activities as the main approach in teaching Islamic values to children. The exemplary method is the most dominant technique because it provides direct examples in daily behavior, while Islamic storytelling is used to convey moral messages in an interesting and easy-to-understand manner for children. Play activities are also integrated with Islamic values, allowing children to learn in a fun and age-appropriate setting. However, this study also found challenges such as limited training for teachers and limited time in implementing the Islamic curriculum to the maximum. Therefore, recommendations for regular teacher training and the development of Islamic modules are prepared as an effort to improve the quality of teaching. The framework resulting from this study makes a significant contribution to the development of an Islamic-based PAUD curriculum that is flexible and adaptive, and is expected to be a practical guide in supporting children's character education from an early age